Tumor intrinsic and extrinsic functions of CD73 and the adenosine pathway in lung cancer - Kowash, Ryan R.; Akbay, Esra A. (Frontiers in Immunology, 2023)
The adenosine pathway is an exciting new target in the field of cancer immunotherapy. CD73 is the main producer of extracellular adenosine. Non-small cell lung cancer (NSCLC) has one of the highest CD73 expression signatures among all cancer types and the presence of common oncogenic drivers of NSCLC, such as mutant epidermal growth factor receptor (EGFR) and KRAS, correlate with increased CD73 expression. Current immune checkpoint blockade (ICB) therapies only benefit a subset of patients, and it has proved challenging to understand which patients might respond even with the current understanding of predictive biomarkers. The adenosine pathway is well known to disrupt cytotoxic function of T cells, which is currently the main target of most clinical agents. Data thus far suggests that combining ICB therapies already in the clinic with adenosine pathway inhibitors provides promise for the treatment of lung cancer. However, antigen loss or lack of good antigens limits efficacy of ICB; simultaneous activation of other cytotoxic immune cells such as natural killer (NK) cells can be explored in these tumors. Clinical trials harnessing both T and NK cell activating treatments are still in their early stages with results expected in the coming years. In this review we provide an overview of new literature on the adenosine pathway and specifically CD73. CD73 is thought of mainly for its role as an immune modulator, however recent studies have demonstrated the tumor cell intrinsic properties of CD73 are potentially as important as its role in immune suppression. We also highlight the current understanding of this pathway in lung cancer, outline ongoing studies examining therapies in combination with adenosine pathway targeting, and discuss future prospects.